The Effect Of Taxpayer Awareness On Regional Tax Receiving On Regional Financial Agency Kaur District - Beti Betriani; Karona Cahya Susena; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the influence of taxpayer awareness on regional tax revenue at the Regional Finance Agency of Kaur Regency. This type of research used descriptive quantitative. The sampling technique used the Slovin technique as many as 100 respondents. The research analysis used simple linear regression analysis. From the discussion regarding the effect of taxpayer awareness on local tax revenue in the Regional Finance Agency of Kaur Regency that has been described, it can be concluded that, based on the results of simple linear regression analysis, the general equation of simple linear regression in this study is: Y = 24.489 + 0.483 X. Where Y is the variable of local tax revenue and X is the variable of taxpayer awareness, while the constant value is 24.489 and the regression coefficient value is 0.483. Taxpayer awareness has a significant effect on local tax revenue in Kaur Regency. This is evidenced by the calculated t value of 6.816. While the value of t table is 1.984 so that t count> t table which results in H0 rejected and H1 accepted, which means that the research hypothesis is accepted.